Isotopic Characterization of the Major Water Source of Rm. Valcea Area, Romania - Vremera, R.; Costinel, D.; Ionete, R.E. (Asian Journal of Chemistry, 2011)
Hydrology and climate studies are an important topic in the current research field due to increased human activity, translated in high demand of fresh water, pollution and global warming. The measurement of oxygen and hydrogen stable isotopes is an essential element in determining the origin, path and history of a water source. Differences between stable isotopes concentrations give an idea about certain hydrological processes that took place. The aim of the present study is to obtain an isotopic fingerprint of the major water source of Rm. Valcea area, the Bradisor reservoir and to present the isotopic variations for oxygen-18 and deuterium along one year. The isotopic composition of the water samples was determined by a continuous-flow isotopic ratio mass spectrometer (CF-IRMS Delta V Plus) coupled with an isotopic equilibration module (GasBench II). The results show a cyclic variation in time of the stable isotopes concentration for the water reservoir, in good correlation with the amount of precipitation and temperatures.